Intra-variability of some biochemical parameters and serum electrolytes in rainbow trout (Walbaum, 1792) bred using a flow-through system. Issue 2 (February 2021) - Fazio, Francesco; Saoca, Concetta; Capillo, Gioele; Iaria, Carmelo; Panzera, Michele; Piccione, Giuseppe; Spanò, Nunziacarla
Abstract: This study aims to evaluate some biochemical parameters and serum electrolytes in cultured rainbow trout Oncorhynchus mykiss (Walbaum, 1792) to evaluate a potential correlation with biometric parameters (weight and length). For this purpose, 100 cultured trout (300–700 g weight range, 25–38 cm length range) bred on a fish-farm were used for the study. Physico-chemical characteristics of water were measured on the farm. Blood samples were collected from each fish to analyze the following parameters: glucose, triglycerides, cholesterol, aspartate aminotransferase (AST); alanine aminotransferase (ALT), calcium (Ca 2+ ), chlorine (Cl − ), iron (Fe 2+ ), phosphorus (P), magnesium (Mg 2+ ), potassium (K + ), sodium (Na + ) and urea. Statistical data analysis showed a significant correlation between size and glucose and cholesterol. No correlation was found between size and other parameters studied. These results represent a contribution to the study of fish size leading to better understanding some biochemical parameters and serum electrolyte profiles in cultured rainbow trout. This research contributes to understanding the intra-individual variability of some blood parameters in cultured rainbow trout O. mykiss offering reliable information on chronic stress status, metabolic disorders and deficiencies in relation to different sizes. These could help in improve the health monitoring in trout fish farms. Abstract : Biochemical parameters; Intra-variability blood parameters; Serum electrolytes; Size; Rainbow trout.